Eyeglasses for Children – a Survey of Daily Practice - Hagander, C. E.; Traber, G.; Landau, K.; Jaggi, G. P. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: Glasses for children are recommended and prescribed by different groups of professionals. We set out to compare the prescription practices of ophthalmologists, orthoptists and optometrists/opticians in Switzerland. Methods: Online questionnaire on the prescription and recommendation of glasses in fictitious cases of children of different ages, refractive values and symptoms. The questionnaire was sent out to members of the Swiss Ophthalmological Society, Swiss Orthoptics and Schweizerischer Berufsverband für Augenoptik und Optometrie. Results: 307 questionnaires were analysed. Optometrists/opticians recommended glasses with a significantly smaller cycloplegic refraction value (p < 0.005) than did orthoptists and ophthalmologists. In the example of a 14-year-old asymptomatic child, ophthalmologists recommended glasses at + 2.64 [Dpt], orthoptists at + 2.44 [Dpt] and optometrists/opticians at + 1.32 [Dpt]. Optometrists/opticians tended to recommend slightly higher correction values in glasses than did ophthalmologists and orthoptists. Conclusion: In Switzerland, optometrists/opticians recommend glasses with significantly smaller cycloplegic refraction values than do orthoptists and ophthalmologists, regardless of age or symptoms described in these fictitious cases.
Keywords: hyperopia; glasses in children; refraction value